Qualitative Research Methods: An essay review - Les McLean; Margaret Myers; Carol Smillie; Dale Vaillancourt (Arizona State University, 1997)
Miller, Steven I. & Fredericks, Marcel (1994) Qualitative Research Methods: Social Epistemology and Practical Inquiry. New York: Peter Lang. 159 pages.